The enterolith causing jejunal obstruction, an unusual presentation: A case report (Indian Journal of Case Reports, 2018)
Enteroliths are a rare cause of intestinal obstruction. Patients can present with repeated episodes of intestinal obstruction as long as an enterolith is able to pass through the gut and then suddenly, they get stuck at the terminal ileum or present with the perforation peritonitis, as may happen in case of a diverticular disease. Here, we report the case of a young male presented to the emergency room with acute intestinal obstruction. During the explorative laparotomy, an enterolith was found stuck inside the proximal jejunum which was removed through an enterotomy. This was an interesting case, as the patient did not have any predisposing factors nor did we find any evidence of other pathologies intraoperatively. Moreover, the enterolith was stuck in jejunum, contrary to the belief that terminal part of the ileum is a most common site for the enteroliths to get stuck.